Control of the Germinal Center by Follicular Regulatory T Cells During Infection - Miles, Brodie; Connick, Elizabeth (Frontiers in Immunology, 2018)
Follicular regulatory T cells (Tfr) are a unique subset of CD4 T cells that control and impact adaptive immune responses in the lymphoid follicles and germinal centers (GC). Since their relatively recent discovery, several studies have revealed that Tfr interact with other cells within this niche and shape ensuing responses. Recent advances defining the functional and developmental characteristics of Tfr have revealed key characteristics of Tfr differentiation, GC recruitment and retention, and regulatory properties. Further, Tfr shape the GC response and balance tolerance through interactions with Tfh, by modifying Tfh number, diversity and function, as well as with B cells. Mechanisms by which Tfr regulate the GC include cell-to-cell interactions with Tfh and B cells, as well as altering their environment through cytokine production and sequestration. Tfr have been shown to have a diverse T cell receptor (TCR) repertoire and can be specific for immunizing agents, demonstrating a potential role in vaccine development. Due to these important characteristics and functions, Tfr play a major role in immune tolerance, response to infection, and vaccine efficacy.